Family related factors associated with caries prevalence in the primary dentition of five-year-old children - Amrita Sujlana; Parampreet Kaur Pannu (Wolters Kluwer Medknow Publications, 2015)
Background: Habits formed in childhood dictate lifestyle choices made as adults. These encompass both oral hygiene and dietary habits which in turn affect dental caries status. Children largely acquire these habits from modeling/observing parents and other family members. Aim: The purpose of this study was to assess the caries status of 5-year-olds, and evaluate associations between dental caries and family-related factors. Materials and Methods: A cohort of 400 children were examined for dental caries using the WHO criteria. Parents were interviewed using a self-structured questionnaire to collect data with regard to variables under evaluation. Statistical analysis: Collected data was subjected to descriptive analysis using the SPSS 12.0 version. Risk factor association with dental caries was investigated using a stepwise logistic regression analysis with P-values < 0.05 considered significant. Results: Fifty nine percent of children suffered from dental caries. Statistically significant risk indicators for a child having dmft > 0 were: Mother with low basic education (OR = 1.3), higher number of siblings (OR = 1.4), high snacking frequency (OR = 2.0), parental inability to control sugar consumption (OR = 1.0) parental laxness about the child's tooth brushing (OR = 1.5), parents brushing their own teeth less than twice daily (OR= 2.0) and unassisted brushing by the child (OR = 1.8). Conclusion: It is thus mandatory to focus on parents' education level, attitudes and family-structure when planning preventive programs for young children.